Introduction to 2017-4 - Buch, Anders (Nordic Journal of Working Life Studies, 2017)
Globalization, rising inequality, polarization, lack of trust, unpredictability, deregulation, destabilization, fragmentation, and flux in working life – and in society in general – seems to be signs of our time. Social scientists have characterized these signs as the postmodern condition, late modernity, liquid modernity, etc., and described how these processes are transforming both our societal institutions and social life in general in undesirable ways. However, in this gloomy characterization of our times, many have been looking toward the Nordic societies to find inspiration for welfare models that might stem the tide of societal disintegration and bring hope of solidarity, social cohesion, regulation, and temper capitalism. The Nordic societies have served as exemplary cases to be emulated by Third Way and progressive politics around the world.  (...)